INHABITING ALTERED MARINE ECOLOGY:ARSITEKTUR ADAPTIF DALAM REDUKSI SAMPAH LAUT SERTA PEMBENTUKAN EKOLOGI KO-EKSISTEN PADA LINGKUNGAN ANTROPOGEN - DAVE Kholifah nur Hidayatullah (Architecture Department, Engineering Faculty, Universitas Diponegoro, 2026)
The accumulation of plastic waste in the oceans, particularly within the Great Pacific Garbage Patch (GPGP), reflects an extreme condition of marine ecosystems in the Anthropocene, where human activities directly reshape global ecological structures. Projections indicate that the amount of floating plastic waste in the oceans could reach approximately 600 million tons by 2040, accompanied by a significant increase in the density of plastic fragments over the past decade. This phenomenon underscores that the marine plastic crisis is systemic, long-term, and extends beyond the issue of material residue alone. The primary impact of this condition lies in the increasingly complex and difficult-to-reverse degradation of marine ecosystems. Microplastics and plastic fragments can no longer be understood as passive pollutants; rather, they function as active agents that interfere with food chains, alter habitat characteristics, and influence the biological and chemical dynamics of marine environments. This situation raises a fundamental question: does this damage signify the collapse of marine ecosystems, or does it mark the emergence of a new ecological configuration shaped by the remnants of human activity? Inhabiting Altered Marine Ecology is proposed as an adaptive architectural approach that begins with the acceptance of a permanently transformed marine ecology. This project positions architecture as an integral part of a degraded ecological system, with an active role in reducing marine waste, managing residual materials, and fostering co-existence among humans, technology, and non-human biota. Architecture is thus understood as an adaptive system that directly engages with ecological crises not to dominate the ocean, but to inhabit and operate within a marine ecology that has been fundamentally altered by human activity.